Analisis Kebutuhan E-book Interaktif Bilingual Etnokimia dengan Pendekatan Konstruktivisme - Henie Poerwandar Asmaningrum; Martha Betaubun; Nasrawati Nasrawati (Universitas Musamus, Merauke, Papua, 2020)
The purpose of this study is to describe the respondents' perceptions of the need for an interactive bilingual e-book with a constructivism approach to the Ethnochemical study material. This research is a descriptive study with a qualitative approach carried out in the Department of English Language Education and the Department of Chemistry Education at Musamus University. The subjects in this study were 11 Chemistry Education students who had taken the Basic English and Contextual Chemistry (Ethnochemistry) courses. The instrument used in this study was an open questionnaire and interview guidelines. Data analysis was carried out through three stages, namely data reduction, data presentation, and drawing conclusions. The results showed that (1) students were not introduced to topics related to local wisdom in the learning Basic English and Ethnochemistry courses, (2) students needed to be facilitated with interactive bilingual e-books with a constructivism approach to Ethnochemical study materials in Basic English and Ethnochemistry courses (3) obtained 5 (five) local wisdom that can be discussed in relation to chemical materials, namely Pineapple, Crown Leaves, Shellfish, Papeda, and Asinan.